Tuberculosis vaccines: barriers and prospects on the quest for a transformative tool. Issue 1 (March 2015) - Karp, Christopher L.; Wilson, Christopher B.; Stuart, Lynda M.
Summary: The road to a more efficacious vaccine that could be a truly transformative tool for decreasing tuberculosis morbidity and mortality, along with Mycobacterium tuberculosis transmission, is quite daunting. Despite this, there are reasons for optimism. Abetted by better conceptual clarity, clear acknowledgment of the degree of our current immunobiological ignorance, the availability of powerful new tools for dissecting the immunopathogenesis of human tuberculosis, the generation of more creative diversity in tuberculosis vaccine concepts, the development of better fit‐for‐purpose animal models, and the potential of more pragmatic approaches to the clinical testing of vaccine candidates, the field has promise for delivering novel tools for dealing with this worldwide scourge of poverty.